PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR BARANG KONSUMSI PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA 2017-2021) - Larasati, Tri Larasati; Fina Fitriyana (Publika Citra Media, 2024)
This research aims to test and obtain empirical evidence regarding the influence of independent commissioners, audit committees and company size on audit delays. This research uses a sample of primary consumer goods sector companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2017-2021. The research method used in this research is the purposive sampling method using Eviews 12 for data analysis.. This type of research is quantitative with a populationof 72 companies and 25 companies used as research samples with 5 (five) years of observation, so the total research sample is 125 samples. The analysis technique used is panel data regression. The result of this research indicate that Independent Commissioners, Audit Committees and Company Size have a significant simultaneous effect on audit delay. Independent Commissioners partially have a significant negative on audit delay, whereas the Audit Committee and Company Size do not have a significant effect on audit delay.